Type A botulinum toxin application as an alternative for gingival smile correction: A literature review - Galdino, Luana Laureano (2021)
The search for aesthetic excellence is one of the goals of dentistry, as it is part of the aesthetics of the smile, as it directly interferes with the patient's self-esteem and quality of life. Conceptually, the gingival smile is the excessive exposure of the gingiva when smiling, and can be considered from 2mm. One of the correction options is with the use of botulinum toxin. In view of this, the aim of this study was to conduct a literature review on current scientific studies on the correction of gummy smile with botulinum toxin type A. Therefore, a search of the main articles published in the last 5 years in the databases: PubMed, SciELO, LILACS and VHL using English as descriptors “smile”, “gummy smile”, “gingiva” and “Botulinum ToxinsType A”. Based on the search result of the 22 articles found, the treatment of gummy smile with botulinum toxin type A acts on the hyperactivity of the muscles involved in the smile, causing a temporary relaxation, which may be an independent technique or an adjunct to other procedures. Showing efficacy, positive esthetic results and low complication rate. However, the main disadvantage is the temporary effect, with an average duration of 4 to 6 months, requiring reapplications over time. Given this context, it can be concluded that the use of this toxin to reduce gummy smile is a safe, fast, effective and conservative procedure option. However, well-designed randomized controlled trials are needed to strengthen the evidence.